2011
DOI: 10.5014/ajot.2011.09205
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Sensory Integration Interventions in Children With Autism Spectrum Disorders: A Pilot Study

Abstract: The purpose of this pilot study was to establish a model for randomized controlled trial research, identify appropriate outcome measures, and address the effectiveness of sensory integration (SI) interventions in children with autism spectrum disorders (ASD). Children ages 6-12 with ASD were randomly assigned to a fine motor or SI treatment group. Pretests and posttests measured social responsiveness, sensory processing, functional motor skills, and social-emotional factors. Results identified significant posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
175
0
11

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 247 publications
(209 citation statements)
references
References 22 publications
12
175
0
11
Order By: Relevance
“…These results consistent with these reported by Abdel Karim and Mohammed who emphasized that sensory integration therapy improves fine motor skills in children with ASD [6]. Sensory integration intervention conducted to children with ASD showed advancement in their individualized goals ability and reduce their mannerism [24]. Also, it has a direct effect on a child's nervous system functioning and capitalizing on plasticity within his or her nervous system [25].…”
Section: Discussionsupporting
confidence: 81%
“…These results consistent with these reported by Abdel Karim and Mohammed who emphasized that sensory integration therapy improves fine motor skills in children with ASD [6]. Sensory integration intervention conducted to children with ASD showed advancement in their individualized goals ability and reduce their mannerism [24]. Also, it has a direct effect on a child's nervous system functioning and capitalizing on plasticity within his or her nervous system [25].…”
Section: Discussionsupporting
confidence: 81%
“…[9,11] The literature supports theory that children with ASD may have somatosensory perception problems. [14,[23][24][25][26] Consistent with the literature, results of the present study indicated that children with ASD have poor somatosensory scores compared with norms of their typically developing peers. [23][24][25][26] However, the literature is still limited regarding somatosensory perception of children with history of trauma.…”
Section: Discussionsupporting
confidence: 80%
“…Diversas investigaciones reportan que cuando una intervención logra normalizar en mayor o menor grado la percepción sensorial, se produce una mejoría importante en el funcionamiento de la persona con autismo, que puede entonces integrar la recepción de estos estímulos de forma organizada y útil (Lang et al, 2012;Pfeiffer, Koenig, Kinnealey, Sheppard y Henderson, 2011). El estudio de las alteraciones sensoriales dentro de la población TEA es un ámbito relativamente nuevo, por lo que es necesario difundir la conciencia de su importancia a la hora de diseñar un plan de intervención.…”
Section: Equilibrio Movimiento (Bal)unclassified